Hyperthermia and Use of Antipyretics in Pediatric Practice - Yu.V. Marushko; K.I. Nagorna (Zaslavsky O.Yu., 2013)
The article deals with problem of hyperthermia in pediatric practice. There are given the peculiarities of fever types, recommendations on management by physician who provides care for a child with a fever, recommendations on the definition of the category of patients who should be administered with antipyretic agent. The authors provide evidence-based data on the benefits of ibuprofen (Nurofen® for children) as the hypothermic therapy in children with fever.